Impacts of climate change and economic and health crises on the agriculture and food sectors - Martinho, Vítor João Pereira Domingues (Practice, progress, and proficiency in sustainability (PPPS) book series., 2022)
"This book discusses new trends in the agricultural and food sectors with themes that propose to make it possible to approximate the various and current dimensions related to food production adding new insights to bring relevant value added for stakeholders"--